THE ROLE OF TRUST IN MEDIATING PERCEIVED SERVICE QUALITY AND INFORMATION QUALITY ON PURCHASE INTENTIONEVIDENCE FROM SHOPEE INDONESIA - Arlan, Fauziah; Hayadi, Ilsya (Universitas Trisakti, 2025)
Perceived service quality and information quality are considered fundamental elements that play a crucial role in fostering close relationships between institutions and their consumers, particularly in the context of online transactions. This study aims to analyze how perceived service quality and information quality influence purchase intention using trust as a mediating variable. This study employs a quantitative approach with the applied analytical method being Structural Equation Modeling (SEM) using the SmartPLS 4.0 software. The results indicate that trust significantly mediates the relationship between perceived service quality and information quality on purchase intention among Shopee app users. The analysis reveals that perceived service quality and information quality directly and significantly influence purchase intention in a positive manner. Trust plays a mediating role. These findings reinforce the concept that trust plays a crucial role as a link between consumers' perceptions of service quality and information quality and their online purchase intentions. The study's results have strategic implications for e-commerce practitioners, particularly Shopee administrators, to consistently maintain service quality, improve product information accuracy, and build trust through transaction security. Thus, companies can foster long-term loyalty amid competition.